Analisis Efektivitas Modal Kerja Terhadap Profitabilitas pada PT Semen Indonesia (Persero) Tbk.: Analysis Of Working Capital Effectiveness Against Profitability on PT Semen Indonesia (Persero) Tbk. - Dana Alfrida Ninia; Ichsan Milang; Sri Mulyaningsih Kamaru (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2021)
The company's activity in utilizing its working capital is quite good because it can create high net sales every year. The increase in the company's net sales jumped in 2019. The increase is not so significant on the working capital side, which means the ability to manage working capital in generating sales is very good. The trend of the development of company profits is declining due to less effective and efficient management of the company's working capital even though the net sales generated increase every year. The contradiction of net sales results with profit after tax and company interest is inversely proportional because, if observed in the company's financial statements, there is an increase in the company's expenditure burden that is large enough to reduce the net profit obtained by the company.